Some regularities in the distribution of kenophytes in the Polish Carpathians and their foreland - Zając, Maria; Zając, Adam (Biodiversity: Research and Conservation, 2015)
The Polish Carpathians and their northern foreland are a rewarding object for the kenophyte distribution research. The study, using the cartogram method, showed that the number of kenophyte species decreases with increasing altitude. Only few kenophytes were found in the lower forest zone. This regularity concerns also the species that reach higher altitudes in the mountains of their native lands. A number of species migrated into the Carpathians through rivers and streams. River valleys generate many open habitats, which are easily colonized by kenophytes due to the lack of competition. In the Carpathians, towns used to be founded in the mountain valleys and this was also a favouring factor of kenophyte propagation. The arrangement of mountain ranges in the Polish Carpathians, including their foreland, hindered the migration of some species and allowed to discover the possible migration routes into the area covered by research. Tracing these migration routes was possible only for those species that have not occupied the whole available area yet. Additionally, the study indicated the most dangerous invasive species in the Polish Carpathians and their foreland.